2019
DOI: 10.1001/jamaophthalmol.2019.1415
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type of Educational System and Prevalence and Severity of Myopia Among Male Adolescents in Israel

Abstract: IMPORTANCE A substantial portion of the public is diagnosed with myopia, which increases the risk of potential sight-threatening complications. The association between study style and the development of myopia is unclear. OBJECTIVE To analyze the association between studying in different educational systems and the prevalence and severity of myopia among Jewish male adolescents in Israel. DESIGN, SETTING, AND PARTICIPANTS A nationwide, population-based study was conducted of 22 823 male candidates for military… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 38 publications
2
73
1
Order By: Relevance
“…The ultraorthodox educational system involves intensive reading starting in early childhood and is similar to the educational system in Taiwan, is associated with the prevalence and severity of myopia. 41 Overall, emerging evidence suggests that near-work plays a major role in myopia development.…”
Section: Discussionmentioning
confidence: 99%
“…The ultraorthodox educational system involves intensive reading starting in early childhood and is similar to the educational system in Taiwan, is associated with the prevalence and severity of myopia. 41 Overall, emerging evidence suggests that near-work plays a major role in myopia development.…”
Section: Discussionmentioning
confidence: 99%
“…In almost all studies, populations with higher levels of education tend to have higher rates of myopia than populations with lower rates of education. For example, a high prevalence of myopia has been reported in populations that receive intensive education at a young age, such as Jewish boys in Israel who received Orthodox or traditional Orthodox education 63 . By contrast, East Asian populations who receive less intensive education have a low and similar prevalence of myopia to that in most western countries 38 .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“… 160 Similarly, the Liwan Eye Study reported that sex differences in older adults were marginal, 161 but in more recent cohorts in China, girls are more likely to be myopic than boys. 11 , 162 The extremely large difference in the prevalence of myopia in girls and boys in Orthodox Jewish communities in Israel, where the boys undergo very intensive education from an early age, shows this trend in reverse, 34 , 35 and contrasts with the similarity of boys and girls receiving more secular education. This variability does not suggest a direct biological link between sex and myopia, but rather suggests that the associations may be mediated by social factors, such as access to education for girls, which varies markedly between locations and has improved considerably in many places in recent decades.…”
Section: Other Risk Factors For Myopiamentioning
confidence: 99%
“…13 The very high prevalence of myopia seen in Israeli Jewish boys attending Orthodox or Ultra-Orthodox schools, compared with that in their sisters, or other children receiving more secular education, is also difficult to explain in genetic terms. 34,35 Again, it is possible to postulate that there is a sex-linked gene variant that predisposes to myopia segregating at a high frequency in Orthodox or Ultra-Orthodox Jewish communities in Israel, and indeed there are examples of rare, sex-linked forms of high myopia. 36 With modern molecular genetic techniques it would be relatively straightforward to identify such a gene variant should it exist; but to date there is no evidence that this is the case.…”
Section: Educationmentioning
confidence: 99%